Short term effect of human lymphocytes viability upon exposure of products with parabens - Saaban, Nurhidasazlina (Universiti Sains Malaysia, 2015)
Personal care products are commonly used in personal hygiene and constitutes of broad classes of chemical compounds. Since 1930s, paraben have been used in cosmetic as preservatives. However, paraben effect has become controversial due to report on estrogenic activity. The aims of this study are to determine the effect of lymphocyte viability and morphological after being administered products with paraben at different concentrations for short term exposure. Blood sample were drew from seven healthy subjects. Lymphocytes were isolated using EasySep Direct Human Total Lymphocyte Isolation Kit. The MTT assay was used to determine lymphocytes viability. Blood smear and stained with Wright's stain were used to determine the morphological changes of the lymphocytes. The result showed significant (p < 0.001) and moderate positive (r = 0.351) correlation between paraben concentration with the percentage of lymphocyte viability. The cell viability recorded for methyl paraben was up to 120%. The lymphocytes rapidly proliferate due to antigen that bind to the receptors and activates the lymphocytes. This showed that products with paraben have toxicity effects towards lymphocytes even after being exposed in short period of time.